REHABILITACJADepression in patients after coronary artery bypass surgery – an unappreciated problem - Foss-Nieradko, Bogna; Piotrowicz, Ryszard (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2008)
Depression prevalence in patients hospitalized for bypass surgery ranges from 16% to 40%. This work discusses the influence of major depression and elevated levels of depressive symptoms on the quality of life and outcome of CABG patients. The psychosocial and pathophysiological mechanisms explaining this inter-relation are singled out. The risk factors of depression appearance in the perisurgical period, methods of depression assessment and treatment options are also discussed.